THE REAL AND IMAGINED ABOUT THE CONFLICT IN CHECHNIA - TEPSAEV, Afti (CENTRAL ASIA AND THE CAUCASUS, 2004)
Nearly all discussions about the military confrontation between Russia and Chechnia boil down to the questions: Who is more to blame for the war, and who needs it now? To prove their point, the sides exploit not only real, but also invent-ed arguments.